Penerapan Hukum Perikatan dalam Kontrak Bisnis UMKM: Studi Kasus Mitra Dagang Hijab Lokal - Rinjani Sindia Lestari; Shahifa Islamia Arrahmah; Zahra Safira Yuniar (Program Studi Ilmu Hukum, Universitas Kuningan, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in the national economy; however, in practice, they often face legal challenges, particularly in the implementation of business contracts. One of the main issues is the ineffective application of the law of obligations in business partnerships, which may lead to disputes and breach of contract. This study aims to analyze the application of the law of obligations in MSME business contracts and to identify legal obstacles faced by business actors in the execution of agreements, using a case study of local hijab trading partners. This research employs a normative juridical method with statutory and conceptual approaches, conducted through a literature review of the Indonesian Civil Code, MSME-related regulations, and relevant legal literature. The findings indicate that MSME business practices still encounter several legal constraints, such as the absence of written contracts, unclear contractual clauses, imbalance of bargaining positions between parties, and limited legal awareness among MSME actors. These conditions result in weak legal protection for business actors in cases of breach of contract. Therefore, enhancing legal awareness, preparing business contracts in accordance with the principles of the law of obligations, and providing continuous legal assistance are essential to ensure legal certainty and fairness in MSME business relationships.